Lipoma arborescens of the knee: a case report of rare entity - Bakrin, Ikmal Hisyam; Ab Rahman, Khairul Shakir; Mahayidin, Hasni; Wan Ab Rahman, Wan Irnawati; Satari, Sazali; Azizan, Asrul Fahmi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Lipoma arborescens is a non-neoplastic, reactive condition due to chronic synovial inflammation and irritation, characterized by frond-like or villous proliferation of mature adipose tissue covered by hyperplastic synovium. The knee is the most commonly affected site particularly the suprapatellar pouch. We report a case of lipoma arborescens affecting the right knee of an elderly Chinese gentleman associated with bilateral knee and hand osteoarthritis. He presented with progressive worsening of right knee swelling and pain. Partial synovectomy of the right knee was performed and no lesion recurrence was noted at one year post-operation. The clinical and imaging findings, pathological features, together with differential diagnoses were discussed.